Luxury brands in China and India - Atwal, Glyn; Bryson, Douglas (Palgrave Macmillan, 2017)
This book provides an analysis of the luxury industry in two of the world's biggest and evolving markets, and identifies and discusses the key issues and dynamics in transforming their luxury landscapes. By discussing the elements that are most likely to dominate boardroom agendas, the pragmatic implications for both strategic and marketing planning are made clear. Special emphasis is placed upon well-contemplated responses to luxury brand marketing challenges that executives are likely to face as they push their brands to adapt and thrive in these shifting markets.-Resumé vydavatel
Keywords: luxusní zboží -- Čína; luxusní zboží -- Indie; marketing; luxuries -- China; luxuries -- India; elektronické knihy; monografie; electronic books; monographs